Development of Affective Aspect Evaluation of Islamic Education (Study Case at 7Th Grade of Muhammadiyah 3 Junior High School Jetis Ponorogo) - Ahmad Saifulloh dan Ferooza Fanny Tjahjono (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2015)
Evaluation is the most important component in improving the qualityof education. In its implementation, the evaluation should include threeaspects: cognitive, affective and psychomotor However, most educationalinstitutions in Indonesia, only carry out an evaluation of cognitive aspects.Yet evaluation of another aspect is also important, especially in IslamicEducation, affective aspect is the most important aspect that must beevaluated and developed. Because the teachings of Islam is not enough onlyto be understood, but also must be practiced and become a way of life forevery Muslim. Muhammadiyah 3 Junior High School Jetis Ponorogo hasa various activities aimed at developing the affective aspect evaluation ofIslamic Education such as: tadarus Quran, Dhuha prayer together and Dhuhurprayer in congregation. The results this paper showed that the efforts ofteacher in developing the affective aspect of Islamic Education in 7th Gradeof Muhammadiyah 3 Junior High School Jetis are already quite good, byusing several approaches, such as the Experience Approach, the HabituationApproach, and the Exemplary Approach.